2006
DOI: 10.1186/1471-2458-6-174
|View full text |Cite
|
Sign up to set email alerts
|

Duration of unemployment and depression: a cross-sectional survey in Lithuania

Abstract: BackgroundIn spite of a growing economy, unemployment is still a severe socio-economic problem in Lithuania. Nonetheless, no studies have been performed about the associations between unemployment and mental health in Lithuania. The aim of this study was to evaluate the associations between unemployment duration and depression in Lithuania.MethodsThe data was collected in a cross-sectional study in 2005. There were 429 filled-in questionnaires received (53.6% response rate) from unemployed persons registered w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
79
2
14

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 32 publications
16
79
2
14
Order By: Relevance
“…38 Employment, despite its economic value, indicates social acceptance and leads to sense of worth. Many previous studies have reported a relationship between unemployment and ill health, 40 poor quality of life 41,40 and depression. 40,42,43 Our study found a relationship between unemployment in PWE and symptoms of depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Employment, despite its economic value, indicates social acceptance and leads to sense of worth. Many previous studies have reported a relationship between unemployment and ill health, 40 poor quality of life 41,40 and depression. 40,42,43 Our study found a relationship between unemployment in PWE and symptoms of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have reported a relationship between unemployment and ill health, 40 poor quality of life 41,40 and depression. 40,42,43 Our study found a relationship between unemployment in PWE and symptoms of depression. Unemployment may be a predictor for depression in epilepsy or the other way around.…”
Section: Discussionmentioning
confidence: 99%
“…Depression is twice as likely to be experienced by people living with diabetes and one in three people with diabetes experience a significant loss in their quality of life due to depression, with the risk for females being higher than for males (Phillips, 2012). Several research studies have reported increased incidence of depression with lower educational levels (Kucuk et al, 2013, Lloyd et al, 2012, Yang et al, 2009, Stankunas et al, 2006, Sivrikaya et al, 2014. Practitioners also need to acknowledge the effects on sexual dysfunction of anti-depressant treatments.…”
Section: Psychological Considerationsmentioning
confidence: 99%
“…Linn, Sandifer and Stein (1985) found that after unemployment, symptoms of somatization, depression, and anxiety were significantly greater in the unemployed than in the employed. Stankunas et al (2006) document high incidence of depression among the long term unemployed in Lithuania; a problem especially acute among disabled persons since they face a relatively high likelihood of finding themselves as long term unemployed as a consequence of their relatively low reemployment probabilities. Both findings lead to a circular relation between unemployment duration and health status, with possible continuous and progressive worsening of employment and health status for disabled persons.…”
Section: Introductionmentioning
confidence: 99%